2000
DOI: 10.2190/44lk-28e9-rrj5-kqvw
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Implementation, and Acceptance of a Primary Care-Based Intervention to Prevent Depression Relapse

Abstract: We conclude that it is feasible to integrate a low intensity, twelve-month relapse prevention intervention for depression into a primary care clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…For example, in an intervention programme for prevention of depression relapse SDM was included. 7 In this study, improvement was found in medication adherence over a 1-year follow-up period. This more recent finding regarding the impact of SDM highlights the potential for the positive effects of SDM in depressed patient populations.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…For example, in an intervention programme for prevention of depression relapse SDM was included. 7 In this study, improvement was found in medication adherence over a 1-year follow-up period. This more recent finding regarding the impact of SDM highlights the potential for the positive effects of SDM in depressed patient populations.…”
mentioning
confidence: 56%
“…3,4 As a response to these issues, in recent years there has been an enhanced focus on the patient in the form of patient-centred interventions to improve depression care, such as Stepped Collaborative Care models for primary care depression treatment. [5][6][7] The patient-provider aspects of these interventions that more centrally involve the patient are gaining attention, in part due to the shared treatment decision-making (SDM) initiatives underway in western Europe and North America. However, little is known about the feasibility and effects of patient-clinician shared decision-making (SDM) for depression treatment.…”
Section: Introduction and Study Objectivementioning
confidence: 99%
“…65 Katon et al Five articles reported the findings of just one study (Katon et al). 45,[57][58][59][60] Although the practitioners in this study were predominantly mental health professionals, and therefore did not strictly meet our part A inclusion criteria, it was unclear whether or not delivery by a mental health professional was mandatory for the implementation of the intervention. Therefore, this study was critically appraised and is summarised in further detail below.…”
Section: Completed Studiesmentioning
confidence: 99%
“…Three depression prevention specialists (a psychologist, a nurse practitioner with a master's degree in psychosocial nursing, and a social worker) received a 60-page training manual 19 and participated in 2 half-day training sessions with a psychiatrist (W.K. ), primary care physician (E.L.), and psychologist (E.J.L.…”
Section: Visits With Depression Specialistsmentioning
confidence: 99%